Spatial behavior of the leaf miner, Leucoptera coffeella (Lepidoptera: Lyonetiidae) in coffee plantations of Temascaltepec, State of México, Mexico - Barrera Rojas, Alejandra; Ramírez-Dávila, José Francisco; Pérez-López, Delfina de Jesús; Rubi-Arriaga, Martin; Pino Miranda, Esther (Revista Colombiana de Entomología, 2023)
The production and commercialization of coffee in Mexico and in the international market is of great importance for the economy of millions of human beings on the planet. InMexico, one of the main pests that causes economic damage is the leaf miner, Leucoptera coffeella (Lepidoptera: Lyonetiidae), which, if not adequately controlled, can cause serious defoliation that in turn could translate into economic losses. Controlling this pest effectively generates a high cost due to the purchase of agrochemicals. Therefore, knowing the spatial distribution of the insect is of great importance since control actions can be directed towards specific areas of infestation so that uniform applications will be reduced. The objective of this work was to determine the spatial distribution of leafminer populations in coffee plantations, based on the information collected, maps of leafminer density were made using the kriging method of spatial statistics. The populations of the pest insect presented an aggregate type distribution and it was reaffirmed with the density maps. The distribution of this pest is well defined in the different areas of the crop, which is useful for proper control in specific areas, thereby reducing the volume of agrochemicals to be used.